Bacteria‐Triggered Release of Antimicrobial Agents1. Issue 2 (29th November 2013) - Komnatnyy, Vitaly V.; Chiang, Wen‐Chi; Tolker‐Nielsen, Tim; Givskov, Michael; Nielsen, Thomas E.
Abstract Medical devices employed in healthcare practice are often susceptible to microbial contamination. Pathogenic bacteria may attach themselves to device surfaces of catheters or implants by formation of chemically complex biofilms, which may be the direct cause of device failure. Extracellular bacterial lipases are particularly abundant at sites of infection. Herein it is shown how active or proactive compounds attached to polymeric surfaces using lipase‐sensitive linkages, such as fatty acid esters or anhydrides, may be released in response to infection. Proof‐of‐concept of the responsive material is demonstrated by the bacteria‐triggered release of antibiotics to control bacterial populations and signaling molecules to modulate quorum sensing. The self‐regulating system provides the basis for the development of device‐relevant polymeric materials, which only release antibiotics in dependency of the titer of bacteria surrounding the medical device.